Design of a Low-Cost Vessel Monitoring System for Fishing Vessels - Gladys Amelia; Totok Yulianto; Adi Novitarini Putri (Jurnal Teknik Perkapalan, 2025)
Indonesia, as the world's second-largest maritime country, has a fisheries sector that plays a crucial role in the economy with a contribution of nearly 5% to GDP. With 170,034 fishing vessels spread across Indonesia's entire territory, monitoring the movement of fishing vessels is essential to prevent illegal activities such as fish smuggling, territorial incursions, and maritime terrorism threats. This study aims to design an affordable, effective, and easy-to-use fish vessel monitoring system. The system includes monitoring of location, fuel, weather, and early warning features that can enhance surveillance efficiency. LoRa technology is used as a communication network module for long-distance data transmission at low cost, while the ESP32 microcontroller manages the system effectively. Initial testing in a laboratory scale model, adjusted to field scenarios, showed satisfactory results: GPS accuracy reached 99.49%, fuel sensor 93.67%, and weather data above 97%, except for wind speed at 72.86% due to external factors during measurement and BMKG data update frequency. Field testing conducted on fishing vessels at the Brondong Nusantara Fishery Port, Lamongan, showed GPS accuracy above 98%, fuel sensor around 92%, and BMKG weather data above 94%. From an economic perspective, this system offers lower production and subscription costs compared to current commercial VMS.